Proceedings of the Design Automation &Amp; Test in Europe Conference 2006
DOI: 10.1109/date.2006.244033
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting a NoC and a Traditional Interconnect Fabric with Layout Awareness

Abstract: Increasing miniaturization is posing multiple challenges to electronic designers. In the context of Multi-Processor System-onChips (MPSoCs), we focus on the problem of implementing efficient interconnect systems for devices which are ever more densely packed with parallel computing cores. Easily seen that traditional buses can not provide enough bandwidth, a revolutionary path to scalability is provided by packet-switched Network-on-Chips (NoCs), while a more conservative approach dictates the addition of band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…Clearly most of the power is consumed by the input modules, as shown by previous work [8,13], but the effect is weaker in soft NoCs than in hard. This also conforms with the area composition of the routers; most of the router area is dedicated to buffering in the input modules, while the smallest router component is the crossbar [1].…”
Section: Router Power Compositionmentioning
confidence: 66%
See 1 more Smart Citation
“…Clearly most of the power is consumed by the input modules, as shown by previous work [8,13], but the effect is weaker in soft NoCs than in hard. This also conforms with the area composition of the routers; most of the router area is dedicated to buffering in the input modules, while the smallest router component is the crossbar [1].…”
Section: Router Power Compositionmentioning
confidence: 66%
“…Other work focuses on complete systems and reports the power budgeted for communication using an NoC [11,12]. Finally, NoCs have been compared to other interconnect types by using application-independent metrics, such as the amount of energy to move a unit of data over different kinds of interconnect [13]. We build on some of the concepts introduced in this literature; however, we also address many FPGA-specific questions that were not addressed in any prior work.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 9, the static NoC consists of 6 switches (1 switch of 8x8, 2 switches of 9x9, 2 switches 10x10 and 1 switch of 11x11), whileboth NoC 1 (for application A) and NoC 3 (for application C) consists of 4 switches (3 switches of 10x10 and 1 switch of 11x11) and NoC 2 (for application B) consists of 4 switches (1 switch of 10x9, 2 switches of 10x10 and 1 switch of 10x11), as shown in Figure 10. The static NoC option, as shown in Table 5, is characterized by a higher area usage, a higher average power consumption (evaluated as proposed in [2]) and a higher average latency, with respect to the three adhoc NoCs specifically designed for each application. Using the specific NoCs, it can be reported reductions of 34% in latency and 24% in power consumption.…”
Section: Express Lines and Topology Reconfiguration Analysismentioning
confidence: 99%
“…Then, designing custom-tailored NoC interconnects that satisfy the performance and design constraints of the SoC for all the different combinations of possible executed applications is a key goal to achieve optimal commercial products [13,2]. However, as general-purpose processor cores are used to run software tasks of different applications in SoCs, the communication between the cores cannot be precharacterized and fully optimized, since the application processes can be mapped differently to the cores, typically with the support of the compiler.…”
Section: Introduction and Problem Descriptionmentioning
confidence: 99%
“…Kim et al have used a star-based NOC for communication using the principle of CDMA (Code Division Multiple Access) [7], Pande et al compared various network topologies for interconnection networks in terms of latency, throughput, and energy dissipation [6]. Adriahantenaina et al proposed a tree-based implementation of NOC [8], where each node in the tree behaves as a router in NOC several researchers have suggested that 2-D mesh architecture for NOC will be more efficient in terms of latency, power consumption and ease of implementation, as compared to other topologies. The Octagon NOC demonstrated in [9] is an example of a novel regular NOC topology.…”
Section: Introductionmentioning
confidence: 99%